2020
DOI: 10.3847/1538-4357/ab6ffc
|View full text |Cite
|
Sign up to set email alerts
|

A Cancellation Nanoflare Model for Solar Chromospheric and Coronal Heating. III. 3D Simulations and Atmospheric Response

Abstract: Inspired by recent observations suggesting that photospheric magnetic flux cancellation occurs much more frequently than previously thought, we analytically estimated the energy released from reconnection driven by photospheric flux cancellation, and proposed that it can act as a mechanism for chromospheric and coronal heating (Priest et al. 2018). Using two-dimensional simulations we validated the analytical estimates and studied the resulting atmospheric response (Syntelis et al. 2019). In the present work, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 74 publications
(87 reference statements)
1
28
0
Order By: Relevance
“…The resulting heating and jet acceleration can occur in the photosphere, chromosphere, transition region, or corona in a way that is evaluated in the model and depends on the sizes of the magnetic fluxes, their separation, and the strength of the overlying magnetic field. The height of the separator and the rate of energy release are calculated analytically and verified in 2D and 3D computational experiments (Syntelis et al 2019;Syntelis & Priest 2020). Then a second cancellation phase occurs as the opposite-polarity fragments undergo actual cancellation and thus drive reconnection at the photospheric footpoints and in the overlying atmosphere.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The resulting heating and jet acceleration can occur in the photosphere, chromosphere, transition region, or corona in a way that is evaluated in the model and depends on the sizes of the magnetic fluxes, their separation, and the strength of the overlying magnetic field. The height of the separator and the rate of energy release are calculated analytically and verified in 2D and 3D computational experiments (Syntelis et al 2019;Syntelis & Priest 2020). Then a second cancellation phase occurs as the opposite-polarity fragments undergo actual cancellation and thus drive reconnection at the photospheric footpoints and in the overlying atmosphere.…”
Section: Introductionmentioning
confidence: 82%
“…Inspired by recent discoveries that flux cancellation is much more common than had previously been recognised and that bright loops often have footpoints in regions where oppositepolarity magnetic flux at the solar surface is cancelling, a theoretical model for the creation of nanoflares by flux cancellation rather than magnetic braiding has been developed (Priest et al 2018;Syntelis et al 2019;Syntelis & Priest 2020). It considers 2018 June 17 UT 00:00 to 2018 June 18 UT 10:00 14 12733…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical simulations have shown that the magnetic topology that determines the height of reconnection along with the line of sight to the reconnection site play a role in the visibility of these small-scale heating events across the wavelength spectrum (Hansteen et al 2019;Peter et al 2019;Ortiz et al Movie associated to Fig. 5 is available at https:// www.aanda.org 2020; Syntelis & Priest 2020). For example, strong emission in the wings of Hα would imply reconnection in the lower atmosphere, whereas bright Mg ii h and k, Si iv 1393.7, 1402.8 Å or even extreme-ultraviolet (EUV) emission would originate in higher layers.…”
Section: Introductionmentioning
confidence: 99%
“…The difference is that EBs and UBs are more likely related to magnetic reconnection occurring in the lower-atmosphere part of the U-shape structures, whereas the reconnection in our observations appears to occur in a relatively higher part (possibly the lower corona) of the U-shape structures. We noticed that a similar process has been theoretically and numerically investigated by Priest et al (2018) and Syntelis & Priest (2020), respectively.…”
Section: Discussionmentioning
confidence: 53%